Cross‐species analysis of nicotine‐induced proteomic alterations in pancreatic cells. Issue 9 (18th April 2013) - Paulo, Joao A.; Urrutia, Raul; Kadiyala, Vivek; Banks, Peter; Conwell, Darwin L.; Steen, Hanno
<x xml:space="preserve">Abstract</x> Toxic compounds in tobacco, such as nicotine, may adversely affect pancreatic function. We aim to determine nicotine‐induced protein alterations in pancreatic cells, thereby revealing links between nicotine exposure and pancreatic disease. We compared the proteomic alterations induced by nicotine treatment in cultured pancreatic cells (mouse, rat, and human stellate cells and human duct cells) using MS‐based techniques, specifically SDS‐PAGE (gel) coupled with LC‐MS/MS and spectral counting. We identified thousands of proteins in pancreatic cells, hundreds of which were identified exclusively or in higher abundance in either nicotine‐treated or untreated cells. Interspecies comparisons of stellate cell proteins revealed several differentially abundant proteins (in nicotine treated versus untreated cells) common among the three species. Proteins appearing in all nicotine‐treated stellate cells include amyloid beta (A4), procollagen type VI alpha 1, integral membrane protein 2B, and toll‐interacting protein. Proteins that were differentially expressed upon nicotine treatment across cell lines were enriched in certain pathways, including nicotinic acetylcholine receptor, cytokine, and integrin signaling. At this analytical depth, we conclude that similar pathways are affected by nicotine, but alterations at the protein level among stellate cells of different species vary. Further interrogation of such pathways will lead to insights into the potential effect of nicotine on pancreatic cells at the biomolecular level and the extension of this concept to the effect of nicotine on pancreatic disease.